MINDFULNESS ISLAMI ALTERNATIF UNTUK TERAPI MODERN - Safinatun Naja (NIHAYAH: Journal of Islamic Studies, 2025)
Abstract The mental health crisis is one of the major challenges in the modern era, marked by the rising prevalence of stress, anxiety, and depression. Conventional psychological approaches such as Mindfulness-Based Stress Reduction (MBSR) and Cognitive Behavioral Therapy (CBT) have proven effective, yet their limitation lies in the absence of a spiritual dimension, which is essential for religious communities. This article aims to explore and offer Islamic mindfulness as an integrative, value-based alternative approach. Employing a qualitative descriptive method through library research, this study draws on academic literature published between 2018 and 2025 to construct a conceptual and practical framework of Islamic mindfulness rooted in Sufi principles such as muraqabah, muhasabah, dhikr, and tafakkur. The findings indicate that Islamic mindfulness is grounded in strong theological sources from the Qur’an and Hadith, and is applicable within modern psychotherapy, particularly for Muslim patients seeking spiritually congruent treatment. Recent studies show that Islamic mindfulness interventions can reduce symptoms of depression, increase inner peace, and strengthen spiritual resilience. Its integration with CBT demonstrates a high level of compatibility, presenting a promising opportunity to develop culturally grounded therapies with a holistic approach. Islamic mindfulness is not merely a substitute for Western methods, but rather a form of psychological recovery deeply rooted in divine consciousness and transcendent spirituality. Further standardized and large-scale research is needed to validate its effectiveness across diverse clinical and socio-cultural settings.